Exploring determinants of agonist efficacy at the CB1 cannabinoid receptor: Analogues of the synthetic cannabinoid receptor agonist EG‐018 - David B. Finlay; Thuy Nguyen; Thomas F. Gamage; Shuli Chen; Daniel G. Barrus; Purvi R. Patel; Brian F. Thomas; Jenny L. Wiley; Yanan Zhang; Michelle Glass (Wiley, 2022)
Abstract Neutral antagonists of GPCRs remain relatively rare-indeed, a large majority of GPCR antagonists are actually inverse agonists. The synthetic cannabinoid receptor agonist (SCRA) EG‐018 was recently reported as a low efficacy cannabinoid receptor agonist. Here we report a comparative characterization of EG‐018 and 13 analogues along with extant putative neutral antagonists of CB1. In HEK cells stably expressing human CB1, assays for inhibition of cAMP were performed by real‐time BRET biosensor (CAMYEL), G protein cycling was quantified by [35S]GTPγS binding, and stimulation of pERK was characterized by AlphaLISA (PerkinElmer). Signaling outcomes for the EG‐018 analogues were highly variable, ranging from moderate efficacy agonism with high potency, to marginal agonism at lower potency. As predicted by differing pathway sensitivities to differences in ligand efficacy, most EG‐018‐based compounds were completely inactive in pERK alone. The lowest efficacy analogue in cAMP assays, 157, had utility in antagonism assay paradigms. Developing neutral antagonists of the CB1 receptor has been a long‐standing research goal, and such compounds would have utility both as research tools and in therapeutics. Although these results emphasize again the importance of system factors in determining signaling outcomes, some compounds characterized in this study appear among the lowest efficacy agonists described to date and therefore suggest that development of neutral antagonists is an achievable goal for CB1.